Prolife of participants in university extension activities associated with good agricultural practices in goat milk production (Research, Society and Development, 2021)
Family farming promotes the permanence of man in the countryside, and increases the supply of fresh and quality food. University extension activities enable social, environmental, economic, and cultural advances, a consequence of the socialization of knowledge, democratization of academic spaces, and acceptance of new paradigms. These favor the implementation of sustainable agricultural practices and the use of available natural resources, in addition to reducing the devaluation of rural work and the marginalization of family farming. The university extension associated with agricultural sciences in the theme of Good Practices in the Production of dairy goats, combines teaching, research and rural extension, through the interaction of educational institutions and the community. The holding of events in the Goat Farming Sector of the Federal Rural University of Rio de Janeiro (UFRRJ), promoted the flow of knowledge among farmers, technicians or students, with the improvement of animal production. There were 80 enrollments, mostly young people, students in agrarian sciences, followed by technical professionals from agrarian and family farmers, interested in knowledge and staying up to date, which helps choosing future strategies to facilitate learning. The identification of sustainability parameters in agricultural properties signaled the importance of supporting in the stages of adaptation and marketing, in order to avoid illegality and food risks. University extension activities aimed at agricultural sciences and dairy goat farming, provide quality professional training, in addition to benefits in the routine of family farmers, in which Good Practices improve the quality of milk and the sustainability of the production system.